93.4k views
0 votes
PLEASE HELP I NEED THIS NOW!!

5(z + 1) = 3(z + 2) + 11 Solve for Z

User Gra
by
6.0k points

2 Answers

4 votes

Answer:

z=6

Explanation:

Isolate the variable by dividing each side by factors that don't contain the variable.

5(z + 1) = 3(z + 2) + 11

5z + 5 = 3z + 6 + 11

5z + 5 = 3z + 17

5z = 3z + 12

2z = 12

2z/2 = 12/2

z = 6

:)

User Shakhmatov
by
5.7k points
2 votes

Answer:

z= 6

Explanation:

5(z + 1) = 3(z + 2) + 11

Distribute

5z+5 = 3z+6+11

Combine like terms

5z+5 = 3z+17

Subtract 3z from each side

5z+5-3z = 3z-3z+17

2z+5 = 17

Subtract 5 from each side

2z+5-5 = 17-5

2z = 12

Divide each side by 2

2z/2 =12/2

z = 6

User Ezvine
by
5.7k points